Safe enough to soar : accelerating trust, inclusion, & collaboration in the workplace - Miller, Frederick A., 1946-; Katz, Judy H., 1950- (Berrett-Koehler Publishers, 2018)
Illustrated by scenarios taken from real-life situations, this book offers concrete actions team members, leaders, and organizations can take to build and maintain a productive, collaborative, and innovative environment in which people do their best work individually and collectively. --